Dental anaesthesia for children – effects of a computer-controlled delivery system on pain and heart rate: a randomised clinical trial. Issue 8 (October 2018) - Patini, R.; Staderini, E.; Cantiani, M.; Camodeca, A.; Guglielmi, F.; Gallenzi, P.
Abstract: Local anaesthesia in dentistry is usually given by conventional injection through a syringe. In this randomised, single-blind, split-mouth clinical study we evaluated the perception of pain and changes in heart rate in children being given dental local anaesthesia using a computer-controlled device compared with that given using a traditional syringe. Participants were in good general health with no contraindications to local anaesthetics. One half of each maxilla was anaesthetised using each technique, the order having been randomly selected according to a computer-generated sequence. The hypothesis was that the controlled anaesthetic flow rate results in virtually imperceptible injections. The outcomes were the perception of pain and the heart rate. Seventy-six children aged from 5–12 years old participated in this study. The mean (SD) pain score of the conventional injection was 5.51 (2.46) and the mean (SD) heart rate was 2.72 (6.76), which were significantly higher than those of the computerised delivery system, which were 4.74 (2.8) and 0.34 (7.3) (p = 0.04). More patients anaesthetised with the traditional syringe technique required a second injection (n = 21). These results suggest that dental anaesthesia given to children with a computer-controlled delivery system reduced pain better than that given with a conventional syringe.